Species diversity and stumpage valuation of timber resources at Pasir Tengkorak Forest Reserves, Langkawi, Malaysia - Abdullah, Muhammad Hafidz (2012)
Tropical forest is highly diverse and provides high economic value. It plays an important role in providing goods and services which contributes to long term social benefits to the community. However, the diversity of coastal forests and its economic value are not well understood because previous studies have been mainly focused on lowland and hill dipterocarp forests. This study was carried out to examine tree composition and estimate its economic value of timber resources in a lowland coastal forest. Four one-hectare plots were set up in Pasir Tengkorak Forest Reserves in Langkawi, Kedah and the subplots measuring 10 m x10 m were established in each subplot. All trees greater than 1 cm dbh and above were identified and the parameters measured include tree height and diameter. The total number of trees recorded above 1 cm in the four hectare plots was 13,543 trees comprises of 50 families, 113 genus and 236 species with the dominant families were Guttiferae, Anacardiaceae and Myristicaceae. Swintonia floribunda is the most dominant species with the most high importance value (IV). The species diversity indices obtained for all four plots were relatively high. The Simpson’s index of diversity ranged from 0.946 to 0.969 with an average of 0.960. The Shannon-Weiner index (H’) ranged from 3.808 to 5.616 with an average value of 5.06. For the species evenness, results showed that the Simpson’s measure of evenness (1/D) ranged from 0.239 to 0.563. The results suggest that species evenness in the four hectare plots is low. The average basal area is 28.57 m2 per hectare while the timber volume is 289.17 m3 per hectare. Stumpage value of timber in the study area is quite high, ranged from RM23,199.87 to RM37,969.37 per hectare with average value of RM 33,600.46 per hectare. Family Anacardiaceae has the highest stumpage value estimated at RM14,379 per hectare which contributes about 42.79% of the total stumpage value. Swintonia floribunda Griff. is the species with the highest stumpage value with RM8373.58 per hectare. The results also indicate that the diameter class that contributes the most to the stumpage value is from diameter class above 60 cm. The regression analysis shows that the relationship between stumpage value and species diversity was significant at the 5% level. Policy implications of the study and recommendations for future research are also highlighted.